Correlation Between Noradrenaline Fluxes, Metabolism and Compartmentalisation in Human Platelets - Legrand, Chantal; Dubernard, Véronique; Meyer, Philippe (Thrombosis and Haemostasis, 1982)
(3H) noradrenaline was taken up by human platelets and partially converted into sulfoconjugated noradrenaline. This uptake was inhibited by drugs which have been previously shown to impair the uptake of 5-HT (ouabain, chlorimipramine) or the storage of 5-HT (tyramine, reserpine) by platelets. In addition, tyramine and reserpine stimulated the formation of sulfoconjugated noradrenaline. The efflux of noradrenaline from platelets was measured in parallel and was found to be directly related to the proportion of non metabolized to metabolized noradrenaline in the cells. Unlike tyramine, which induced a similar release of noradrenaline and 5-HT, reserpine was less effective at inducing noradrenaline release than 5-HT release. This study indicates a preferential localization of noradrenaline in the granular pool of human platelets with the existence of an extragranular sulfoconjugated pool which is increased when the granular storage of noradrenaline is impaired. Studies of noradrenaline fluxes and metabolism may be useful in the understanding of both acquired and inherited platelet storage pool defects.
Keywords: Platelets; Noradrenaline; Storage; Metabolism; Fluxes